Eksperimen Analisis Pertambahan Panjang Pegas Terhadap Perubahan Massa Benda Pada Praktikum Virtual Laboratory - Trissanggrah Nirmala Desinta; Adam Malik (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2024)
In this research, researchers analyzed the increase in spring length in relation to the changing load or mass of the object (variations in the mass of the object) using Phet Simulation or a virtual laboratory which can be used on the website platform. The aim of this research was carried out using the Phet Simulation virtual laboratory, to determine the relationship between length and mass of objects in spring experiments to enable more effective and efficient use of tools and materials and by using this virtual laboratory it can make it easier for teachers and participants to carry out practicums remotely. distant and independent. The method used in research in this virtual laboratory is experimentation and using a quantitative approach. The results of the graphic analysis obtained show that the relationship between force and increase in spring length is linear or directly proportional, which means that the increase in spring length (x) is proportional to the force applied (F). This means that the greater the force applied, the longer the spring will stretch, which is in accordance with Hooke's Law theory.